Transcriptional activation of plant defense genes by fungal elicitor, wounding, and infection. - Lawton, M A (1987)
Activation of plant defense genes was investigated by analysis of transcripts completed in vitro by isolated nuclei. Elicitor treatment of suspension-cultured bean (Phaseolus vulgaris L.) cells caused marked transient stimulation of transcription of genes encoding apoproteins of cell wall hydroxyproline-rich glycoproteins (HRGP) and the phenylpropanoid biosynthetic enzymes phenylalanine ammonia-lyase (PAL) and chalcone synthase (CHS), concomitant with the onset of rapid accumulation of the respective mRNAs and hence expression of the phytoalexin (PAL, CHS), lignin (PAL), and HRGP defense responses. While there was a lag of 2 h prior to stimulation of HRGP gene transcription, induction of the transcription of PAL and CHS genes occurred within 5 min of elicitor treatment. Induction of transcription of PAL, CHS, and HRGP genes was also observed in wounded hypocotyls and in infected hypocotyls during race-cultivar-specific interactions with the fungus Colletotrichum lindemuthianum, the causal agent of anthracnose. Transcriptional activation occurred not only in directly infected tissue but also in distant, hitherto uninfected tissue, indicating intercellular transmission of an endogenous signal for defense gene activation. It is concluded that transcriptional activation of defense genes characteristically underlies induction of the corresponding defense responses and expression of disease resistance.